Roman Religion in the Time of Augustus - Bondioli, Nelson de Paiva (Numen, 2017)
This article first discusses the term “Roman religion” and the different views and meanings that it possesses, favoring an analysis of the sacra publica. It then considers the model of the polis-religion, both its common usage and its relevance or adequacy in the study of Roman religion. These discussions are followed by an analysis of the articulation of the idea of the mos maiorum within Augustan religious reforms.